A tunable process: catalytic transformation of renewable furfural with aliphatic alcohols in the presence of molecular oxygen1. Issue 17 (28th February 2015) - Tong, Xinli; Liu, Zonghui; Yu, Linhao; Li, Yongdan
<x xml:space="preserve">Abstract</x> The tunable efficient transformation of furfural with aliphatic alcohols in the presence of molecular oxygen is achieved in the presence of a nano Au catalyst.